The effect of dividend announcements on the price and volume of stock trading at the Stock Exchange in 2007 (analysis of paired sample t-test) - Fakhri Nurzaman (Institute of Accounting Research and Novation (IARN), 2022)
The main purpose of this study is to investigate the effect of dividend announcements on price and trading volume of stock. The effect is reflected from a significant difference between prices and trading volume of stock before and after dividend announcement. The object of this study is a company listed on the Indonesia Stock Exchange and doing dividend announcement in 2007. The study period is between 5 days before dividend announcement and 5 days after dividend announcement. The method using paired sample t-test to compare prices and trading volume of stock means between 5 days before dividend announcement and 5 days after dividend announcement. The results of this study show that the price and trading volume of stocks have a significant difference before and after the dividend announcement.